ARE OUTCOMES FOLLOWING LAPAROSCOPIC RESECTION FOR INFLAMMATORY BOWEL DISEASE IN ADULTS AND CHILDREN COMPARABLE?. (8th June 2013) - McMullin, C; Morton, J; Vickramarajah, S; Brennan, M; Salvestrini, C; Torrente, F; Heuschkel, R; Davies, R J
Abstract : Introduction: Inflammatory bowel disease (IBD) has prevalence in Europe of approximately 2.2 million, with evidence of increasing incidence in the paediatric population. Up to 40% of patients will require surgery for their disease, the majority within the first year of diagnosis. Aims/Background: Since 2007, a single surgeon whose main practice is in adults has performed laparoscopic resectional surgery for IBD in adults and children within separate IBD multidisciplinary teams. Our aim was to assess short-term outcomes for adults and children following laparoscopic resectional surgery for IBD. Method: Analysis of a prospectively collected database was carried out to include all patients who had undergone a laparoscopic resection for IBD (excluding stoma formation alone and ileoanal pouch surgery) under the care of one surgeon between December 2007 and July 2012. Results: Fifty-nine patients underwent laparoscopic resections (28 children and 31 adults). Median age for children was 14 (range 8–16) years and adults 32 (range 21–63) years. The median BMI for adults was 23 (range 18–38) and 19.5 (range 13–29.5) for children (p= 0.0006). Operative times for adults and children were similar with a median of 210 and 165 minutes respectively (p=0.09). Postoperative complication rates were not significantly different: 6 (19%) in the adult population and 4 (14%) in children (p=0.73). Median length of stay was 5 days in adults vs 6 days in children (p=0.09). Conclusion: Laparoscopic surgery in children is safe when performed by an experienced surgeon whose normal practice is in adults, with acceptable outcomes when compared to adults.